Impacts of Climate Change in Bangladesh and its Consequences on Public Health - Kibria, Golam; Pavel, Hasinur Rahman; Miah, Md. Rashed; Islam, Md. Raisul (Journal of Sustainability and Environmental Management, 2022)
Climate change can affect many aspects of our lives, for example, health and environment, access to natural resources, safety and security, agriculture and food production. Health issues are the most crucial and burning difficulties for human beings in all of these aspects. The scope of this review considered commonly used methodologies for climate change-induced diseases research and assessment of climate-induced health problems throughout Bangladesh. Surveys, key informant interviews (KII), focus group discussion (FGD), registered hospital visit patient data as well as and other similar methodologies are found popular in this research area. Negligible studies are found that used experimental method including laboratory analysis and registered hospital visit of patient information. Very few experimental studies observed water sample tests and human health-related samples like urine and blood pressure. People living in the coastal part has climate-induced crisis like salinity intrusion, cyclone, storm surge that lead to health problems like diarrhea, cholera, skin diseases, typhoid, chicken pox. While people living in both drought-prone and flood prone areas have health problems like diarrhea, cholera, fever, and skin diseases. People living in the urban and the hilly regions have climate induced crisis of increased temperature and they suffer from vector-borne diseases. Waterborne communicable diseases are the most common climate-induced diseases found in this review. Waterborne non-communicable diseases like hypertension, pre-eclampsia, eclampsia and gynecological problems during pregnancy are common and women suffers a lot. Blood pressure and related cardiovascular diseases, jaundice, and respiratory issues are also getting worse day by day which has strong connection with climate change effects like temperature, rainfall and salinity.